Bioactive toothpastes in dentin hypersensitivity treatment: A systematic review - Samantha Ariadne Alves de Freitas; Neurinéia Margarida Alves de Oliveira; Juliana Larocca de Geus; Soraia de Fátima Carvalho Souza; Adriana de Fátima Vasconcelos Pereira; José Bauer (Saudi Dental Journal)
Purpose: The use of bioactive materials is a recent proposal in the treatment of dentin hypersensitivity (DH) due to the ability to stimulate the neoformation of a barrier on dentin surface. Questions have arisen about the effectiveness of the materials to reduce DH when compared to the control groups (placebo or non-bioactive substance). Thus, the aim of this systematic review was to evaluate the randomized controlled trials in adult patients for DH treatment with a dentifrice containing bioactive glass, applied either at-home or in-office. Methods: The study was registered in PROSPERO and followed PRISMA guidelines. Searches were carried out in four databases (Pubmed/Medline, CENTRAL, Wbb of Science, LILACS) spanning from February 2020 to March 2020, with no language or publication date restrictions. A supplementary hand-search was performed by checking the list of references. The so-called gray literature of the national and international databases for theses and dissertations, as well as unfinished, in progress and unpublished studies were also searched. Results: After reading the titles and abstracts, articles that were duplicated (74 records) or unrelated to the systematic review (76 records) were excluded. Fifteen studies were evaluated considering seven at low risk of bias, four at high risk and four at moderate risk. Conclusion: The bioactive compounds at low concentrations (2.5–7.5%) can be used as treatment of DH both at-home and in-office.